The first Americans : the story of where they came from and who they became - Aveni, Anthony F.; Nelson, S. D. (New York : Scholastic Nonfiction, 2005)
Presents an illustrated history of the first North American civilizations including the Cahokia, Anasazi, Hopewell, and Moundbuilders, and describes their culture, religion, society through archaeological evidence.
Map on endpaper.
Includes index.
5.3
3-6
Keywords: Paleo-Indians -- Migrations -- Juvenile literature; Paleo-Indians -- Origin -- Juvenile literature; Human beings -- Bering Land Bridge -- Migrations -- Juvenile literature; Indians of North America -- History -- Juvenile literature; Indians of South America -- History -- Juvenile literature; Paleo-Indians.; Paleo-Indians -- Origin; Human beings -- Bering Land Bridge; Indians of North America -- History; Indians of South America -- History; Paleo-Indians.; Paleo-Indians -- Origin; Human beings -- Bering Land Bridge; Native Americans -- North America -- History; Native Americans -- South America -- History